On some Features of the Grain and Subgrain Size in a Cu-Cr-Zr Alloy After ECAP Processing and Aging - K. Abib; B. Alili; T. Baudin; A.-L. Helbert; F. Brisset; L. Litynska-Dobrzynska; P. Zieba; D. Bradai (Archives of Metallurgy and Materials)
A Cu-1Cr-0.1Zr alloy has been subjected to ECAP processing via route Bc and aging at 250-800°C. Electron BackScatter diffraction (EBSD), Transmission Electron Microscopy (TEM) and X-Ray Diffraction Line Profile Analysis (XRDLPA) techniques have been used to unveil some peculiarities of the grain and subgrain structure with a special emphasis on the comparison of the grain size estimated by the three techniques. For the alloy ECAP processed and aged up to 16 passes, the grain size (from EBSD, 0.2 < d < 5 μm), subgrain size (from TEM, d ~ 0.75 μm) and “apparent” average crystallite size (from XRDLPA, d < 0.25 μm) are manifestly different. The results were compared to the published data and analyzed based on the fundamental aspects of these techniques.